Coronation of Sugreeva - 079 - Saurabh Saxena (2022)
Image courtesy : Saurabh Saxena - https://puratattva.in/ Rama instructs that while Sugreeva is coronated the king of Kishkinda, Vali's son Angada be crowned the prince.